Clinical case of Parry–Romberg syndrome - V. B. Voitenkov (Nervno-Myšečnye Bolezni, 2019)
PParry–Romberg syndrome, also known as progressive hemifacial atrophy, is a rare clinical entity of unknown origin with atrophy of skin and subcutaneous fat changes. A classic case of Parry–Romberg syndrome in a woman age 43 is presented. Initial facial changes appeared at the age of 20 years amid complete well-being and in the next 21 years a subcutaneous fat atrophy of the left half face developed, resulting in characteristic deformity changes. No other complaints and manifestations of the disease (epileptic seizures, headache, involvement of the other half of the face and/or extremities) were present at the timeof survey. The analysis of blink reflex, galvanic skin reflex, needle electromyography of the m. orbicularis oris from two sides, computed tomography of the skull bones revealed no pathological changes. The face infrared thermography confirmed asymmetric reduction of temperature on the ipsilateral side. Magnetic resonance scan showed hypotrophy of the left masticatory muscle, the left submandibular salivary gland, thinning of subcutaneous fat layer, changes in the white matter of the brain. Despite the typical clinical features the Parry - Romberg syndrome is a diagnostic challenge known and it is necessary to inform doctors about the latest achievements in the study of etiology, management and prognosis of the disorder.